Co-Precipitation of Acetaminophen and Eugragit Rl 100 Using Supercritical Anti-Solvent in Controlled Drug Delivery - Chong, Gun Hean (2009)
The controlled drug release has been proven to enhance the bioavailability of a drug by maintaining the drug concentration in therapeutic level within certain period of time and lowering the risk of drugs side effects by reducing the frequency of drug administration. Among the available drug administration systems, microcapsule has provided advantages over the conventional mode, due to higher efficiency and flexibility. This microcapsule can be produced by supercritical fluids (SCF) method which currently been used in composite particles production. This application solves the limitations of conventional pharmaceutical methods for the production of active ingredient loaded micro particles. Supercritical anti-solvent (SAS) is one of the SCF methods proven to have good potential in micronization of pure component. In this technique, SCF acts as an anti-solvent for the feed solution and the precipitation occurs when these two media (SCF and feed solution) contact each other. Therefore, the general objective of this study is to widen the application of SAS in the co-precipitation of two components namely acetaminophen in Eudragit RL 100 towards controlling the delivery of the drug. The investigation began with the development of a mathematical model to estimate the rate of mass transfer between a solvent droplet and CO2 during SAS process in the supercritical regime. The simulation results show that, the solvent droplet expands when the solvent is denser than CO2, and shrinks when the CO2 is denser than the solvent. Both of these phenomena occur in less than one second. Based on the developed mathematical model, SAS system with 490ml of precipitation vessel is designed and developed. The design work focuses on the precipitation vessel, particle collector, temperature control system, process stream and selection of spraying device. After the commissioning of the SAS completed, the system is used to determine the optimum operating conditions for co-precipitation of acetaminophen in Eudragit RL 100. The optimum conditions are determined based on the encapsulation efficiency, particle size, product recovery and loading efficiency. The optimum conditions are 110 bars, 35 °C, 1.75 ml/min feed flow rate and 35 mg/ml polymer concentration. The repeatability and consistency of the SAS system is also determined to ensure the accuracy of the results. At least 90% consistency is achieved in the co-precipitation of acetaminophen in Eudragit RL100 as judged by the particles size. In addition, the analysis of fourier transform infra red (FTIR) and thermo gravimetric analyzer (TGA) prove that the association between the acetaminophen and Eudragit RL 100 is physical. The results also show that the SAS process do not change the chemical structure (FTIR and high performance liquid chromatography (HPLC)) and thermal stability (TGA and differential scanning calorimetry (DSC)) of acetaminophen during the process. However, the crystallinity of treated acetaminophen is marginally reduced compared to the untreated acetaminophen (x-ray diffraction (XRD)). More importantly, SAS process has successfully improved the homogenity and size of acetaminophen which is evidenced from the image of scanning electron microscope (SEM). The diffusion coefficient for the release of the processed acetaminophen is also determined by Fick’s second law in this study. In is found that the diffusion coefficient is affected by the particle size and polymer concentration. The estimated diffusion coefficient has a magnitude of 10-14 m2/s. In conclusion, SAS technique has been proven to be one of the promising alternative techniques for co-precipitation of two solutes in drug microcapsules production for controlled drug delivery.